(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Retinoic acid receptor-related orphan receptors (ROR, nomenclature as agreed by the NC-IUPHAR Subcommittee on Nuclear Hormone Receptors [10]) have yet to be assigned a deﬁnitive endogenous ligand, although RORα may be synthesized with a ‘captured’ agonist such as cholesterol [63, 62].